1981
DOI: 10.3758/bf03214284
|View full text |Cite
|
Sign up to set email alerts
|

Spatial selectivity in visual search

Abstract: To what extent does successful search for a target letter in a visual display depend on the allocation of attention to the target's spatial position? To investigate this question, we required subjects to discriminate the orientation of a briefly flashed U-shaped form while searching for a target letter. Performance operating characteristics (POCs) were derived by varying the relative amounts of attention subjects were to devote to each task. Extensive tradeoffs in performance were observed when the orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
120
1
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(137 citation statements)
references
References 24 publications
(47 reference statements)
13
120
1
3
Order By: Relevance
“…First, if attention was space based on multiple-U'C trials but not on single-LlC trials, we would expect spatial priming effects, in the form offaster and more accurate performance when the target properties appeared in the same display location than when they appeared in different locations in subsequent trials, for the multiple-DC condition but not for the single-DC condition (Cave & Pashler, 1995; J. E. Hoffman & Nelson, 1981;Kim & Cave, 1995). However, an analysis of our data failed to reveal spatial priming effects for either the single-DC trials or the multiple-U'C trials in the present experiment.'…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, if attention was space based on multiple-U'C trials but not on single-LlC trials, we would expect spatial priming effects, in the form offaster and more accurate performance when the target properties appeared in the same display location than when they appeared in different locations in subsequent trials, for the multiple-DC condition but not for the single-DC condition (Cave & Pashler, 1995; J. E. Hoffman & Nelson, 1981;Kim & Cave, 1995). However, an analysis of our data failed to reveal spatial priming effects for either the single-DC trials or the multiple-U'C trials in the present experiment.'…”
Section: Discussionmentioning
confidence: 99%
“…E. Hoffman, Houck, McMillian, Simons, & Oatman, 1985; 1. E. Hoffman & Nelson, 1981;Kramer & Hahn, 1995).…”
mentioning
confidence: 99%
“…Eriksen and Hoffman (1972) showed that flanking distractors only interfered with a target if they were nearby. Hoffman and Nelson (1981;Hoffman, Nelson, & Houck, 1983) found that performance was better in dual task experiments if the stimuli for both tasks were near one another. Participants in experiments by Cave and Pashler (1995) were better able to identify a succession of digits when they all appeared at the same location than when they appeared at different locations.…”
Section: The Special Role Of Locationmentioning
confidence: 99%
“…A likely candidate is the spatial attention system, a mechanism that can operate within a fixation to selectively process information from different locations (Eriksen & Hoffman, 1973, 1974Hoffman, 1975;Hoffman & Nelson, 1981;Posner, 1980;Posner, Nissen, & Ogden, 1978). Allocating attention to a position in space results in faster and more accurate processing of luminance and form information in a region of space surrounding that location (Bash inski & Bacharach, 1980;Downing, 1988;Hawkins et al, 1990;Hoffman & Nelson, This research was supported by University of Delaware Biomedical Research Grant and Army Research Office Contract DAAL03-86-k-0080 to the first author and was submitted by the second author in partial fulfillment of the requirements for a Master of Arts degree. The authors are indebted to Lou Logan French for helpful comments on an earlier version of this paper.…”
mentioning
confidence: 99%